Assessment of nutritional status of upper and middle class females (30 – 50 Years) in Askari XI, Rawalpindi, Punjab- Pakistan - Khattak, Muhammad Muzaffar Ali Khan; Akram, Z. (2006)
Location and purpose of the study: This study was conducted in the Askari XI, (Eleven) Rawalpindi, Punjab, Pakistan. The purpose of this study was to compare the nutritional status of two socio-economic classes i.e. upper and middle class females using different approaches apart from body mass index (BMI). Study design: Fifty houses were randomly selected from the Scheme, 25 in each class on the basis of rank of the retired military officers. From each house a female in between the age range of 30-50 years was selected and interviewed. Materials and methods: The age and anthropometric measurements i.e. weight, height, activity levels and food intakes (for 24 hours recall) were recorded in a questionnaire. For both classes age group (30 – 40 & 41 – 50) and activity levels (light & moderate) were determined. From weight and height data BMI was calculated. The macronutrients namely protein, carbohydrate, fats and micro-nutrients namely minerals, (calcium, phosphorus and iron) and vitamins (A & C) were determined by using the Food Composition Table for Pakistan. The energy contents of the food eaten by the respondents were calculated by multiplying the daily eaten protein carbohydrates and fats with 4, 4 and 9 respectively. Body mass index and dietary intakes were used for the evaluation of the nutritional status. This was accomplished by comparing the observed BMI with the BMI ranges for nutritional status. The observed nutrients intakes data was compared with the American Dietetic Association, World Health Organization and Health Welfare Canada Nutrition Recommendation. Results: The means were compared with the aforementioned norms. In the upper class the underweight, ideal weight, over weight and obese were 4, 24, 52 and 20 percent respectively, whereas in the middle class underweight, ideal weight, over weight and obese were 0, 48, 48 and 4 percent respectively. The upper class was having lower energy intake by 40-49% and the protein intake was sufficient. When compared on the age basis, the two age groups were also having decreased energy intake by 40-46%. Similarly, on the basis of activity both light and moderate were having lower energy intake by 40-49% and the protein consumption was according to the standard. On overall basis i.e. socio-economic class, age and activity level, the respondents were having increase over reference protein and carbohydrate, while decrease over reference fat intake. Similarly, the three comparisons were applied for minerals and vitamins intakes. The respondents were having lower calcium and iron intakes by 31-34% and 39-44% respectively. The vitamin A intake was also lower by 22-43%. Conclusions: This data suggest that socioeconomic status is not the only factor causing the reduced energy and nutrients intakes.